Evaluation of clinical profile, radiological and functional outcome following anterior cervical discectomy and fusion for cervical compressive myelopathy - Kumar, Ranjit; Tiwari, Brijesh Kumar; Pandey, Sanjeev Kumar (International Surgery Journal, 2020)
Background: Symptomatic cervical disc prolapse is best managed with anterior cervical discectomy with or without fusion. We studied the clinical, radiological and surgical profile with postoperative outcome of the patients undergoing anterior cervical discectomy and fusion (ACDF) for cervical compressive myelopathy at one level. Methods: In this retrospective study, data was collected from patients who underwent ACDF for cervical compressive myelopathy in our hospital between 2016 and 2019. Clinical, radiological profile with surgical outcome were studied. Results: A total of 283 patients were recruited. They could be followed up for a period of at least 6 months and so were recruited for the study. Out of these 283 patients (201 males; 82 females; mean age, 48.4 years, range, 22 years to 83 years), magnetic resonance imaging (MRI) cervical spine without contrast and x-ray cervical spine was available for all the patients. Nape of neck pain was the most common presenting symptom followed by tingling sensation in all four limbs and trunk. Average time taken for surgery was 2 hours 10 minutes with an average blood loss of 50 ml. Mean follow up duration was 2.7 years (range 6 months to 4 years). Conclusions: ACDF is the treatment of choice for the patients with clinical and radiological evidence of cervical cord compression. The techniques is associated with minimal blood loss and exceptionally good surgical outcome. Following discectomy, putting an autologous graft or titanium cage improves the spine stability and maintains the cervical lordosis.